Childhood Stroke: Awareness, Interest, and Knowledge Among the Pediatric Community - Michaela V. Bonfert; Katharina Badura; Katharina Badura; Julia Gerstl; Julia Gerstl; Ingo Borggraefe; Florian Heinen; Sebastian Schroeder; Martin Olivieri; Martin Olivieri; Raphael Weinberger; Mirjam N. Landgraf; et al. (Frontiers Media S.A., 2018)
Objective: Acute childhood stroke is an emergency requiring a high level of awareness among first-line healthcare providers. This survey serves as an indicator of the awareness of, the interest in, and knowledge of childhood stroke of German pediatricians.Methods: Thousand six hundred and ninety-seven physicians of pediatric in- and outpatient facilities in Bavaria, Germany, were invited via email to an online-survey about childhood stroke.Results: The overall participation rate was 14%. Forty-six percent of participants considered a diagnosis of childhood stroke at least once during the past year, and 47% provide care for patients who have suffered childhood stroke. The acronym FAST (Face-Arm-Speech-Time-Test) was correctly cited in 27% of the questionnaires. Most commonly quoted symptoms of childhood stroke were hemiparesis (90%), speech disorder (58%), seizure (44%), headache (40%), and impaired consciousness (33%). Migraine (63%), seizure (39%), and infections of the brain (31%) were most frequently named as stroke mimics. Main diagnostic measures indicated were magnetic resonance imaging (MRI) (96%) and computer tomography (CT) (55%). Main therapeutic strategies were thrombolysis (80%), anticoagulation (41%), neuroprotective measures, and thrombectomies (15% each). Thirty-nine percent of participants had taken part in training sessions, 61% studied literature, 37% discussed with colleagues, and 25% performed internet research on childhood stroke. Ninety-three percent of participants approve skill enhancement, favoring training sessions (80%), publications (43%), and web based offers (35%). Consent for offering a flyer on the topic to caregivers in facilities was given in 49%.Conclusion: Childhood stroke constitutes a topic of clinical importance to pediatricians. Participants demonstrate a considerable level of comprehension concerning the subject, but room for improvement remains. A multi-modal approach encompassing an elaborate training program, regular educational publications in professional journals, and web based offers could reach a broad range of health care providers. Paired with a public adult and childhood stroke awareness campaign, these efforts could contribute to optimize the care for children suffering from stroke.